Implementasi Kurikulum Merdeka dalam Meningkatkan Kemampuan Membaca pada Kelas 1 di SDN 88 Kota Bengkulu - Lestari, Puja; Oktima Santi, Cinci; Putri Hazani, Meisi; Puspitasari, Yeni (JPT : Jurnal Pendidikan Tematik, 2024)
This research aims to investigate the implementation of the Independent Learning Curriculum in an effort to improve reading skills in grade 1 students at State Elementary School (SDN) 88 Bengkulu City. This research uses a qualitative approach with a case study design. This research was carried out at SD Negeri 88 Bengkulu City on November 11 2023. The subjects studied were the principal, class 1 and class 4 teachers, at SDN 88 Bengkulu City. Research was carried out through interviews, observation and documentation. The research results show that even though the Independent Learning Curriculum has been implemented at SDN 88, there are still significant challenges in involving grade 1 students, especially those who have not been in kindergarten before. This article provides an overview of the obstacles faced by teachers and students in the learning process, as well as presenting poten-tial strategies to increase the effectiveness of the implementation of the Independent Learn-ing Curriculum in developing reading skills at grade 1 level at SDN 88 Bengkulu City. The implications of this research can contribute to further understanding of the challenges and solutions in dealing with the problems of learning to read at the initial level of basic education.